Analisis Bibliometrik terhadap Penggunaan Kata Kunci Santri dan Nasionalisme pada Database Dimensions - Agniya Rihadatul Aisy (UIN Sunan Gunung Djati Bandung, 2023)
The rise of Islamophobia makes students and clerics seen as radical groups or circles and are often mistaken for terrorists. Because of that, the study of Santri and Nationalism is an interesting topic to study for various circles. The purpose of this research is to map an overview of Santri and Nationalism using bibliometric analysis to assess the performance of scientific articles while at the same time explaining research themes related to Santri and nationalism, research trends, publication locations, and researcher productivity. This research data was obtained from the Dimensions website for the 2013-2022 period which was then exported to 2021 excel format. The results of this analysis show a very striking development trend in 2017 in the philosophy research and religious studies categories and the most productive researcher is Nur Hidayanto Pancoro Putro and the most published journal is Studia Islamika. With the rise of the phenomenon of Islamophobia, the study of students and nationalism is an interesting topic to study more deeply.